Системна модель двохконтинуумної механіки діелектриків як основа електродинаміки і теорії світового ефіру - Khoroshun, L. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A new conception of constructing the theory of connected processes of mechanics and electrodynamics in deformed solids, based on two-continuum mechanics of dielectrics, is proposed. There are considered the phenomenological and discrete-structural methods of constructing equations that transform to a system of connected equations concerning displacements of neutral molecules and intensity of an electric field. The equations satisfy the principle of Galilei-Newton relativity, describe the longitudinal electric and transversal electromagnetic waves with dispersion in moved and deformed dielectrics. The Maxwell equations are a particular case of the constructed equations. The model of word ether is formulated as an ideal fluid dielectric. The constructed theory allows to explain the experiments of Fizeau, Michelson and starlit aberration in limits of classic physics without Einstein postulates.